Students' Thinking Skills in Solving HOTS Standardized Problems Based on the SOLO Taxonomy of Economics Subjects at Senior High School - Seri Ningsih; Riyo Riyadi; Sudarman; Vitria Puri Rahayu (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to determine the thinking ability of SMA Negeri 1 Sangasanga students in solving HOTS standardized questions based on SOLO Taxonomy in economics subjects. The subjects of this study were students of class XI.3 who chose economics as a specialization subject. The type of research conducted in this study uses descriptive with a qualitative approach. The data analysis technique used is written test analysis and is elaborated with several stages which include data reduction, data presentation and verification. The results showed that the thinking ability of students in class XI.3 SMA Negeri 1 Sangasanga in solving economic problems with HOTS standards was quite good and diverse. Of the 31 students, none were at the Pre-structural level, 26% reached the Uni-structural level with 8 students, 61% reached the Multi-structural level with 19 students and 13% had reached the Relational level with 6 students.